Combination of GIS, MCDA and AHP for the Selection of Most Suitable Location for Primary Health Care Facilities (American Journal of Geospatial Technology, 2023)
This study reveals the necessity of offering a solution to the Primary Health Care (PHC) facility site location issue in the healthcare industry. PHC is a crucial component of healthcare that serves as the first point of contact for individuals, families, and communities. It allows for the delivery of care as close as possible to people’s homes and places of employment, but over time, a solution to this sector’s location issues has been neglected. The purpose of this study is to locate the optimum locations in the study area for new PHC facilities. After careful evaluation of various literature, oversight organizations, and local government officials, the raw data needed were obtained. The effectiveness of a Geographical Information System (GIS), Multi-Criteria Decision Analysis (MCDA), and the Analytical Hierarchy Process (AHP) were integrated to provide a novel method for choosing acceptable locations for PHC facilities in the Ado Local Government Area. The specified criteria layers were overlaid using a weighted linear combination (WLC) approach, such as Map algebra. The results showed that within the land mass of the research region; only 10% were deemed to be the most suitable areas, while 53% of the places were suitable, and 37% of the areas were unsuitable. As a result, the study suggests that the integration of GIS, AHP, and MCDA methods is beneficial in addressing the issue of site appropriateness assessments for PHC facilities.